The Effect of Monitoring and Evaluation Practices on the Performance of Projects: A Case of Children Survival Project Implemented by Compassion International Kigali, Rwanda - Uwitonze, Josephine; Bugingo , Emmanuel (Journal of Entrepreneurship & Project Management, 2024)
The general objective of this study was to assess the effect of monitoring and evaluation practices on the performance of children survival projects in Compassion International Kigali. The study had the following specific objectives: establish the effect of the M&E planning process on the performance of the children survival project in Kigali; examine the effect of communication in M&E on the performance of the children's survival project in Kigali; find out the effect of human resource capacity in M&E on the performance of the children survival project in Kigali; and assess the effect of M&E stakeholders’ involvement on the performance of the children's survival project in Kigali. The study population was 138 staff members of the Child Survival Project, Compassion International Rwanda, in the city of Kigali. The sample size of 103 was determined with the help of the Solvin formula. Simple random sampling used in the research's selection of study participants. Random sampling employed due to its ease and the fact that all participants are employees of the Child Survival Project at Compassion International Rwanda, which ensures that each individual has an identical possibility of being chosen. The study applied the following tools of data collection: questionnaires and documentary techniques. The researcher used the descriptive and correlation analyses computed by Statistical Package for Social Sciences 23. The Model Summary presents the results of a multiple regression analysis that includes the predictors M&E Stakeholders Involvement, Human Resource Capacity, M&E Planning Process, and Communication in M&E in relation to the dependent variable Project Performance. The value of R (0.859) indicates a strong positive correlation between the combined predictors and the dependent variable, highlighting the interplay of these factors in influencing project performance. The coefficient of determination (R Square) is 0.738, indicating that approximately 73.8% of the variability in Project Performance of Child Survival Program can be explained by the combined influence of the four predictors. Children survival projects should ensure a comprehensive and well-structured M&E planning process that clearly defines measurable goals, identifies relevant indicators, employs efficient data collection methods, aligns with beneficiary needs, facilitates communication, and enables timely interventions.